Risk factors for central lymph node metastasis in patients with papillary thyroid carcinoma: a retrospective study - Du, Jiachen; Yang, Qing; Sun, Yixuan; Shi, Peng; Xu, Hao; Chen, Xiao; Dong, Tianyi; Shi, Wenjing; Wang, Yatong; Song, Zhenzhi; Shang, Xingchen; Tian, Xingsong (Frontiers in Endocrinology, 2023)
Introduction: Thyroid cancer is the most prevalent endocrine malignancy, with its global incidence increasing annually in recent years. Papillary carcinoma is the most common subtype, frequently accompanied by cervical lymph node metastasis early on. Central lymph node metastasis (CLNM) is particularly the common metastasis form in this subtype, and the presence of lymph node metastasis correlates strongly with tumor recurrence. However, effective preoperative assessment methods for CLNM in patients with papillary thyroid carcinoma (PTC) remain lacking.Methods: Data from 400